2018
DOI: 10.1166/jbn.2018.2499
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Cell Penetrating R11 Peptide for Diagnosis of Bladder Cancer

Abstract: As compared with normal bladder tissue, FITC-R11 is a more specific molecular probe for BCa, and has the potential application in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…43 Unlike gene therapy using viral method, these vectors are internalized into cells through lipid raftdependent macropinocytosis rather than endocytosis and specific receptor as in the CAR. 43,44 p53 transcription factor composed of 3 domains; activation domain, sequence-specific DNA binding domain, and oligomerization domain. There are 2 sequence-specific DNA binding domains.…”
Section: Non-viral Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Unlike gene therapy using viral method, these vectors are internalized into cells through lipid raftdependent macropinocytosis rather than endocytosis and specific receptor as in the CAR. 43,44 p53 transcription factor composed of 3 domains; activation domain, sequence-specific DNA binding domain, and oligomerization domain. There are 2 sequence-specific DNA binding domains.…”
Section: Non-viral Methodsmentioning
confidence: 99%
“…Besides, some of them were entrapped in macropinosome which hindered them to be fused into the target region. 44,48 However, recent research on haemagglutinin-2 protein had shed light that may lead us to solution of this problem. This NH2-terminal 20 amino acid peptide of the influenza virus haemagglutinin-2 protein (HA-2) with its pH-based fusogenicity got the entrapped 11R-p53 to be released from macropinosome so that the molecule could swim right through towards the target region, and got fused with the mt-p53 C-terminus at pH 5, thus turning on the latent p53 protein to action.…”
Section: Non-viral Methodsmentioning
confidence: 99%
“…Nuclear targeting Has certain cytotoxicity May be a delivery vector for agents used in treating bladder diseases. [ 36 , 42 ] …”
Section: Screening Of Peptidementioning
confidence: 99%
“…This selectivity can also be utilised to deliver imaging agents to tumour cells. For example, Du et al found that the oligoarginine, R11, is able to deliver a fluorescent probe to bladder tumours, producing a more intense signal than that seen in normal bladder tissue [26]. More extensive reviews of the applications of CPPs as anti-cancer therapies and diagnostics can be found in [22] and [23].…”
Section: Applicationsmentioning
confidence: 99%